From the heyday of the railroads to neglect: historical context and state of deterioration of the New Railway Station in Campina Grande-PB - Carvalho, Gabriel Lincoln Lopes; Silveira, José Augusto Ribeiro da; Silva, Emmanoel Marques da; Silva, Paulo Roberto de Oliveira; Canova, César Renato (Revista Nacional de Gerenciamento de Cidades, 2022)
The history of railway stations in Brazil played a structuring role in many cities in the country, reflecting exponential growth in various spheres of society. The deactivation of railway stations and/or their disuse in several municipalities and the lack of appropriation by cities and users of this urban transport equipment are a risk to their resistance/existence, weakening the important historical-cultural-social role to which they belong. The New Railway Station (Estação Ferroviária Nova) in Campina Grande city, Paraíba state, representing one of its facilities and greatly influencing the development of the city, is an example of the detrimental process due to the public and private sectors´ neglect, with its buildings (listed by IPHAEP) in ruin and without any pretensions of public policies to soften and/or reverse this process. This work aims to discuss the importance and structuring role of the New Railway Station in Campina Grande, as well as the historical and formal aspects that characterize signs of abandonment and how they can impact the uses and appropriations by the users. To accomplish this, steps were needed to collect information, such as field surveys; bibliographic and documentary research; literary reviews; databases in the city hall, among other forms of data composition. The present study resulted in a dynamic overview and chronological understanding of the apex of the New Railway Station, from its inauguration to its decadence; through historical, formal, social, and heritage expressions, it was possible to understand in which context the station was placed and the processes followed until its current state of deterioration.